0772 Effects Of Solriamfetol On 24-hour Blood Pressure Patterns In Participants With Excessive Daytime Sleepiness Associated With Narcolepsy. (27th May 2020) - Strollo, P J; Malhotra, A; Strohl, K; Pepin, J; Schweitzer, P; Lammers, G; Hedner, J; Baladi, M; Carter, L; Bujanover, S; Menno, D; Dauvilliers, Y
Abstract: Introduction: Solriamfetol is a dopamine and norepinephrine reuptake inhibitor indicated to improve wakefulness in adult patients with excessive daytime sleepiness associated with narcolepsy (75-150 mg/d) or obstructive sleep apnea (37.5-150 mg/d). Previous studies reported small mean increases in blood pressure (BP); however, the time course of these effects has not been evaluated. In addition, effects on BP dipping, which has been shown to be a risk factor for adverse cardiovascular outcomes, have not been evaluated. These analyses evaluated the effects of solriamfetol treatment on BP using 24-hour ambulatory blood pressure monitoring (ABPM) and on the percentage of narcolepsy patients with a non-dipping BP profile. Methods: Twenty-four-hour ABPM was conducted at baseline and week 8 in a 12-week randomized controlled trial in participants with narcolepsy (n=236). Results: At week 8, increases in BP were apparent in the 150 and 300 mg dose groups from 8 AM until 4 PM and 6 PM, respectively. At baseline, 52% (placebo) and 48% (combined solriamfetol) of participants were non-dippers (defined as <10% decrease in mean arterial pressure [MAP] during sleep). There was no increase in the percentage of non-dippers at week 8 relative to baseline (placebo, 44%; combined solriamfetol, 39%). Results were similar when dipping was defined by changes in systolic BP and diastolic BP. Conclusion: The effects of solriamfetol on BP at the highest approved dose of 150 mg/d are transient across the day. Solriamfetol was not observed to have an increase in non-dipping classification in participants with narcolepsy at any dose studied. Support: Jazz Pharmaceuticals